Role of Analytical Marketing Skills for Enhancing Job Market Appraisal - Riyadi - Riyadi; Andi - Setiawan; Bagus Yunianto Wibowo; Saptianing - Saptianing; Kurniani - Kurniani (Admisi dan Bisnis, 2022)
The problem of perceived employability and employee performance has become a debate that affects higher education. Our study investigates the interaction of the relationship between perceived work ability and employee performance appraisals. Our study found discriminatory perceptions of employability between various job skills in students and job opportunities and demands. Our study also highlights the value through multiple perspectives that lead to marketing analytical skills with a distinctive competitive advantage. Our study positions marketing analytical skills as mediating the relationship between perceived employability and employee performance. Ultimately the aim of our study is to help bridge the gap between graduate skills and future labor market needs. The analysis used a sample of 107 using an online questionnaire and the data obtained were analyzed using structural equation modeling. The findings of this study show that marketing analytical skills make the relationship between core marketing skills, customer insights skills and job market appraisal more valuable for the concept of employability